Decolorization and biodegradation of the Congo red by Acinetobacter baumannii YNWH 226 and its polymer production's flocculation and dewatering potential. (October 2015) - Li, Ruijing; Ning, Xun-an; Sun, Jian; Wang, Yujie; Liang, Jieying; Lin, Meiqing; Zhang, Yaping
Highlights: Congo red was degraded by Acinetobacter baumannii YNWH 226 under aerobic conditions. The mechanism of adsorption and degradation of Congo red by the strain was studied. Congo red was first used as the sole carbon source for production of bioflocculant. A relation of EPS between decolorization and flocculation, dewatering was discussed. Abstract: The strain Acinetobacter baumannii YNWH 226 was utilized to degrade Congo red (CR) under aerobic conditions. CR was employed as the sole carbon source to produce extracellular polymeric substances (EPS) used as potent bioflocculants in this strain. A total of 98.62% CR was removed during the 48-h decoloration experiments using CR (100 mg/L). A total of 83% bioadsorption and 65% biodegradation were responsible for the decoloration and degradation of CR through the strain. The bioflocculant showed high flocculation activity and dewaterability on textile dyeing sludge. A maximum flocculation of 78.62% with a minimum SBF of 3.07 × 10 9  s 2 /g and a CST of 58.4 s were achieved. We investigated the internal relationship between the decolorization efficiency of YNWH 226 and the flocculation activity and dewatering capacity of its EPS. The components and structure of the EPS highly influenced the decolorization efficiency of CR and the flocculation activity and dewatering capacity on sludge.